Advances in Databases and Information Systems, Lecture Notes in Computer Science - Ibrahim, A.; Turdukulov, Ulanbek; Kraak, M. (Springer, 2014)
Recent data acquisition tools have resulted in huge amounts of data that have spatial and temporal components. The movement represents an important category of such data. Some phenomena may have attributes that vary continuously over space, such as wildfires and storms. Nevertheless, for simplification purpose, most applications represent such phenomena as objects by neglecting their internal continuous structure. Moreover, little consideration has been given to such characteristics in moving objects database. At this end, this paper presents a data model for managing raster data and internal heterogenous attributes in moving objects. The data model utilizes the abstract data types. We add two abstractions (moving raster, and combined type) to describe the change of the raster data and internal varying characteristics of the moving objects along with specific operations that permit to analyse them. Query examples are provided to demonstrate the application of these operations.